Asset prices and inflation-targeting : implications for South Africa - Cosser, Leigh Emma (Rhodes University, Faculty of Commerce, Department of Economics, 2005)
An analysis of the current monetary policy framework in South Africa, which followed the exampie of a number of developed countries by implementing an inflation-targeting regime in 2000, is presented. The primary goal of the framework is to establish price stability, with financial stability a secondary objective. However, as has been evident in other countries, price stability does not guarantee financial stability. Movements in asset prices and the development of asset price bubbles have resulted in a number of episodes of financial instability, which negatively impacted on the growth and development of the countries involved. In addition, the majority of these episodes have occurred in periods of low and stable inflation. The dissertation analyses whether monetary policy would be more efficient if asset price movements were incorporated within the inflation-targeting regime. International experience indicates that early intervention of monetary policy can dampen the negative effects that result when an asset price bubble "bursts". However, if the monetary authorities act too early the effects on the economy can be just as disruptive. The literature is scrutinized to establish what the most effective form of monetary policy should be. The results are then transposed within the South African context to establish how the South African Reserve Bank can best ensure both price and financial stability.
Keywords: South African Reserve Bank; Monetary policy -- South Africa; Inflation (Finance) -- South Africa; South Africa -- Economic policy; Banks and banking, Central -- South Africa; Anti-inflationary policies; Monetary policy -- Japan; Monetary policy -- United States